Post marathon cardiac troponin T is associated with relative exercise intensity - Richardson, A. J.; Leckie, T.; Watkins, E. R.; Fitzpatrick, D.; Galloway, R.; Grimaldi, R.; Baker, P. (Journal of Science and Medicine in Sport, 2018)
Objectives: This study aimed to investigate whether measures of cardiopulmonary fitness and relative exercise intensity were associated with high sensitivity cardiac troponin T (cTnT) rise after a road marathon. Methods: Fifty-two marathon runners (age 39 ± 11 years, body mass 76.2 ± 12.9 kg, height 1.74 ± 0.09 m) attended the laboratory between 2 and 3 weeks prior to attempting the Brighton Marathon, UK. Running economy at 10 km h-1 (RE10) and race pace (RERP), ventilatory threshold (VT) and VO2max tests were completed. CTnT was measured within 48 h prior to the marathon and within 10 min of completing the marathon, using a high sensitivity assay. Heart rates (HR) were recorded throughout the marathon. Results: Runners demonstrated a significant increase in cTnT over the marathon (pre-race 5.60 ± 3.27 ng L-1, post-race 74.52 ± 30.39 ng L-1, p < 0.001). Markers of endurance performance such as running economy (10 km h-1 223 ± 18 ml kg-1 km-1; race pace 225 ± 22 ml kg-1 km-1), VT (38.5 ± 6.4 ml kg-1 min-1) and O2max (50.9 ± 7.7 ml kg-1 min-1) were not associated with post-race cTnT. Runners exercise intensity correlated with post-race cTnT (mean HR %VT 104 ± 5%, r = 0.50; peak HR %VT 118 ± 8%, r = 0.68; peak HR % O2max 96 ± 6, r = 0.60, p < 0.05) and was different between the low, medium and high cTnT groups (p < 0.05). Conclusions: CTnT increases above reference limits during a marathon. Magnitude of cTnT rise is related to exercise intensity relative to ventilatory threshold and O2max, but not individuals` absolute cardiopulmonary fitness, training state or running history.